Active surveillance for adverse events following immunization. (February 2014) - Crawford, Nigel W; Clothier, Hazel; Hodgson, Kate; Selvaraj, Gowri; Easton, Mee Lee; Buttery, Jim P
<x xml:space="preserve">Abstract</x> Comprehensive surveillance of adverse events following immunization (AEFI) is required to detect potential serious adverse events that may not be identified in prelicensure vaccine trials. Surveillance systems have traditionally been passive, relying upon spontaneous reporting, but increasingly active surveillance and supplemental strategies are being incorporated into vaccine safety programs. These include active screening for targeted conditions of interest (e.g., hospitalization), monitoring of new data sources and real-time methodologies to detect changes in vaccine safety data in these sources. The role of improved causality assessment in AEFI surveillance is discussed, with its important role in determining whether a temporal association may have occurred by chance alone. Strong local vaccine safety networks are required to support national immunization programs, with recent progress in developing a framework for low- and middle-income countries. Global collaboration is increasingly required to address challenges in active AEFI surveillance, particularly for rare serious adverse events.